From observation to lesson planning: describing a Pragmatic-based experience with Portuguese as an Additional Language (PAL) students - Travincas de Castro, Leonardo; Silveira Jorge da Silva, Mônica (BELT - Brazilian English Language Teaching Journal, 2023)
This paper was written as a prerequisite for the completion of the course Pragmatics applied to the teaching of Portuguese as an additional language (PLA), offered by the Postgraduate Program in Literature at PUCRS. During a field visit, it was observed that foreign students of a given group were verbally interacting with their Portuguese teacher producing discourses with a degree of formality lower than that required by the speech situation. After signing consent forms, the students were asked to fill out a form to gather general personal information. Then, the group was filmed performing a task and, after that, a Discourse-Completion Task (DCT) was applied, verifying the recurrence of the linguistic inadequacy previously identified. To deal with the problem, it was decided to develop three lesson plans, and the goal here is to describe how this process happened. The plan presents diversified activities and adaptations of didactic sequences usually aimed at teaching grammar to a work focused on Pragmatics, especially on Politeness Theory. It is hoped that this text can contribute to raising teachers’ interest in teaching about the adequacy between linguistic production and context, as well as providing practical ideas for the classroom.